THU0366 Association of Chromosome 1Q32 with Ankylosing Spondylitis Is Independent of Bowel Symptoms and Faecal Calprotectin. (15th July 2016) - Roberts, R.L.; Wallace, M.; Harrison, A.; White, D.; Dalbeth, N.; Stamp, L.; Ching, D.; Highton, J.; Merriman, T.; Robinson, P.; Brown, M.; Stebbings, S.
Abstract : Background: Colonoscopic, endoscopic, and histological studies have demonstrated that intestinal inflammation, similar to the ileo-colitis seen in Crohn's disease (CD), is a common feature of ankylosing spondylitis (AS). More recently, the existence of a shared genetic basis to CD and AS has been demonstrated [1, 2]. Objectives: To test whether the association of known CD risk loci with AS is primarily due to the presence of bowel inflammation in AS patients. Methods: 286 Caucasian patients fulfilling the modified New York criteria for AS and with no history of inflammatory bowel disease were assessed non-invasively for bowel inflammation using faecal calprotectin and the Dudley Inflammatory Bowel Symptom Questionnaire (DISQ) [3]. All patients and 568 matched healthy controls were genotyped with TaqMan® SNP genotyping assays for the confirmed CD risk loci [2], 1q32 (rs11584383), JAK2 (rs10758669), CDKAL1 (rs6908425), IL12B (rs100454310), ZPBP2 (rs2872507), MUC19/LRRK2 (rs11175593), STAT3 (rs744166), and IL23R (rs1343151, rs10489630, rs11209026). Chi square testing was used to test for association. Results: Minor alleles of 1q32 SNP rs11584383 (p=0.002, OR=0.69, 95% CI 0.55–0.87), and IL23R SNPs rs11209026 (p=0.011, OR=0.53, 95% CI 0.32–0.87) and rs1343151 (p=0.027, OR=0.77, 95% CI 0.61–0.97) all conferred protection against AS. However, only the association of 1q32 SNP rs11584383 remained significant after Bonferroni correction for multiple testing (p=0.02). The Cochran's Q test found no significant difference between ORs after stratification of AS patients by DISQ score and faecal calprotectin (Pdifference >0.09). Conclusions: Previously, the association of CD risk loci with susceptibility to AS has been attributed to the co-occurrence of asymptomatic intestinal inflammation which is well recognised and supports the concept that CD and AS are two extremes of a related genetic and phenotypic disease spectrum. However, our study provides preliminary evidence that the association of the confirmed CD risk locus 1q32 SNP rs11584383 with AS is independent of bowel inflammation. References: Parkes M, et al. 2013. Nature reviews Genetics. 14(9):661–673. Danoy P et al. 2010. PLoS genetics. 6(12):e1001195. Stebbings S et al. 2012. Rheumatology. 51(5):858–865. Disclosure of Interest: None declared